Evaluasi Parkir Kendaraan Kampus Universitas (Studi Kasus Kampus II Universitas Prof. Dr. Hazairin, SH Bengkulu - Inditha Indriani; Elly Tri Pujiastuti (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
ABSTRACT Every year at Campus II, Universitas Prof. Dr. Hazairin SH, number of students who enroll in this university keep increasing each year, it making more demand for new parking spot in this university. Because of that, parking characteristic analytic like field survey are needed to make sure the parking problem can be solve. The aim of this research is to learning the characteristic such as, parking capacity, parking accumulation, parking volume, parking cycle, parking index,and parking needed at this univesity. The results of this research are: a) maximum accumulation four wheel vehicle are 9 vehicles, and maximum accumulations for two wheel vehicle are 72 vehicles; b) university blabla has 20 square parking capacity for four wheels vehicle, and two vehicle, and 53 square for two wheels vehicle.; c) 19% Index parking for cars and 115% for bikes which mean available car parking spot can hold the vehicle, but for bike parking spots cannot handle more at the peak hour. d) Average parking volume is 22 cars and 234 bikes in one day, e) Parking turn over for cars is 2,2 cars/hour and 29,09 bikes/hour; f) average parking duration for two kinds of vehicle can be catagorized as mid term parking.